2021
DOI: 10.1055/s-0041-1726225
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Endoscopy Drink of Simethicone and N-Acetylcysteine Significantly Improves Visualization in Upper Gastrointestinal Endoscopy

Abstract: Introduction With the advancements in diagnostic and therapeutic upper gastrointestinal endoscopy (UGIE), clear mucosal visualization is essential to ensure optimal outcomes. Though routinely followed in Japan and Korea, pre-endoscopic preparation is seldom used in India. We evaluated the efficacy of a pre-endoscopic drink of N-acetylcysteine (NAC) and simethicone in improving mucosal visibility during UGIE. Patients and Methods This study was a retrospective, investigator blind study with a case–control study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…5,6,36 Another 4 randomized trials supporting the use of simethicone pre-gastroscopy have been published after these meta-analyses. [42][43][44][45] European guidelines recommend adding simethicone to bowel prep before colonoscopy 46,47 Two meta-analyses found simethicone added to the bowel prep improved mucosal visibility and bowel cleanliness. 30,31 Three RCTs found simethicone increased the adenoma detection rate.…”
Section: Simethicone Is Given Orally Before An Endoscopy But Not Flus...mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,36 Another 4 randomized trials supporting the use of simethicone pre-gastroscopy have been published after these meta-analyses. [42][43][44][45] European guidelines recommend adding simethicone to bowel prep before colonoscopy 46,47 Two meta-analyses found simethicone added to the bowel prep improved mucosal visibility and bowel cleanliness. 30,31 Three RCTs found simethicone increased the adenoma detection rate.…”
Section: Simethicone Is Given Orally Before An Endoscopy But Not Flus...mentioning
confidence: 99%
“…Three meta-analyses support the use of simethicone given orally before gastroscopy showing that simethicone improves mucosal visibility and increases lesion detection 5,6,36. Another 4 randomized trials supporting the use of simethicone pre-gastroscopy have been published after these meta-analyses 42–45…”
Section: Introductionmentioning
confidence: 99%
“…Addition of GOV3 in Sarin's classification will make it more comprehensive, uniform, and reproducible for future studies. Anikhindi et al, 2 in their case-control study demonstrated that a safe, cheap, and easily available pre-endoscopy drink of N-acetylcysteine with simethicone can significantly improve mucosal visibility during upper gastrointestinal endoscopy. This helps in ensuring optimal endoscopic outcomes.…”
Section: Best Original Articlesmentioning
confidence: 99%